The Role of Teachers in Improving the Quality of Reading the Qur'an for Early Class Santri - Zulhasif Hermawan; Mochammad Asnawi (Educazione: Journal of Education and Learning, 2023)
This study investigates the role of teacher modeling in improving Qur'anic recitation, specifically tajweed, among students at Indonesian pesantren (Islamic boarding schools). Despite the widespread use of teacher modeling in religious education, its direct impact on tajweed mastery has been underexplored. Tajweed is a critical aspect of Qur'anic recitation that ensures the accurate pronunciation of Arabic letters and the correct application of pronunciation rules. This research examines how teachers' demonstrations of proper recitation techniques influence students' ability to apply tajweed rules effectively. Data was collected through semi-structured interviews with teachers and direct classroom observations, focusing on their pedagogical practices and the students' responses. The findings reveal that teacher modeling is a key factor in enhancing students' tajweed skills, as it provides a clear, practical example for students to imitate. The study also identifies the benefits of a structured, step-by-step teaching approach, where students progress from basic letter recognition to more complex tajweed rules. These findings have significant implications for improving Qur'anic education in pesantren, emphasizing the importance of teacher-led demonstrations in fostering accurate Qur'anic recitation. This research contributes new insights into effective teaching strategies and offers practical recommendations for enhancing tajweed instruction in Islamic education.